Ice margin oscillations during deglaciation of the northern Irish Sea Basin. (31st July 2018) - Chiverrell, R. C.; Smedley, R. K.; Small, D.; Ballantyne, C. K.; Burke, M. J.; Callard, S. L.; Clark, C. D.; Duller, G. A. T.; Evans, D. J. A.; Fabel, D.; van Landeghem, K.; Livingstone, S.; et al.
ABSTRACT: We present a new chronology to constrain ice‐margin retreat in the northern Irish Sea Basin. Estimates on the timing of ice thinning derived from surface exposure ages for boulders from the summits of the Isle of Man and south‐west Cumbria suggest that ice thinning was commensurate with the rapid retreat that followed the short‐lived advance of the Irish Sea Ice Stream (ISIS) to maximum limits in the Celtic Sea. This ice retreat in the northern Irish Sea Basin was fastest at 20 ka in response to a wider calving margin, but slowed as ice stabilized and oscillated against the Isle of Man. We provide the first age constraints for the Scottish Readvance (19.2–18.2 ka) and demonstrate that it was a potentially regional event across the Isle of Man and Cumbrian lowlands not linked with Heinrich Event 1. After the Scottish Readvance, the ice front retreated northwards towards the Southern Uplands of Scotland at the same time as climate north of ∼45°N warmed in response to summer insolation. This sequence demonstrates the importance of internal dynamics in controlling ice retreat rates in the Irish Sea, but also that deglaciation of the northern Irish Sea Basin was a response to climate warming.